Habituasi Mahasiswa Psikologi Islam Semester VII Perguruan Tinggi Berbasis Pesantren dalam Menghadapi Tugas Akhir - Muhammad Irfan Ardiansyah; Nainul Muna; Irmawan Jauhari (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to describe the habituation of seventh-semester students at Islamic boarding schools (pesantren) in facing the demands of their final assignments. The background of this study is the habituation of seventh-semester Islamic Psychology students at two different educational institutions who must carry out their assignments according to applicable regulations and their respective curricula. This research method used a qualitative descriptive approach, with Islamic Psychology students participating in Aswaja (Aswaja) courses as subjects. Data were obtained through observations of learning activities and interviews. Results of this study: Through the habituation process, students are expected to develop a disciplined, orderly, and religious lifestyle. Habituation to academic routines and Islamic boarding school activities not only serves as a form of adaptation to the environment but also as a means of developing religious, resilient, and professional character. Thus, habituation plays a crucial role in helping students manage their time, maintain a balance between academic and spiritual demands, and increase learning effectiveness in facing the challenges of the final year of study.